Reactions to nation-building: The roots of Amhara nationalism in Ethiopia and its implications - Yilkal Ayalew Workneh (Cogent Social Sciences, 2024)
This article shows reactions to nation-building practices induced in the last decades of the imperial regime and its antithetical replacement of the current political system. It examines how the post-1991 political discourse and its institutions contributed to Amhara identity formation and mobilization and the latter’s implications for the current political discontent in Ethiopia. The article engages with the discursive narratives—’Amhara domination discourse,” ideological othering, and institutional flaws—that reinforce the development of Amhara nationalism. Using a qualitative research methodology, it gathers data from sources such as documents, broadcast and social media, and key informant interviews to argue that the origins of the Amharas’ sense of victimization lie in good part in the replacement of centralized one-nation nationalism with a non-representative devolved system; having been left out during the institutionalization of the current political system, the Amhara now demand to be integrated into that system. The repercussions of Amhara nationalism have been visibly seen in the political dynamics of the Amhara region and the deadly conflict that Ethiopia faces after the war with the Tigray region that could attract neighboring countries and regional players to it. Hence, launching an inclusive peace settlement and designing a legitimate political system are necessary to mitigate the current political discontent.